Theoretical Study on HFC-61 Mixture as an Alternative Refrigerant to R502 - Xuan Yongmei; Chen Guangming (Zhileng xuebao)
A ternary HFC-161 mixture (HFC-161/125/143a with mass ratio 10/45/45) was proposed as an alternative refrigerant to R502. Theoretical results indicated that it is an environmentally friendly refrigerant with zero ODP (ozone depletion potential) and a GWP (global warming potential) value of 3466, which is lower than that of R502, R404A and R507. The thermophysical properties and theoretical cycle performance of HFC-161 mixture under low temperature working conditions and varying working conditions were calculated and compared with R502, R404A and R507 by software Refprop. The calculation results indicated that the operating pressure, pressure ratio, COP and cooling capacity per unit volume of HFC-161 mixture are equivalent to those of R502, and its temperature glide is smaller than that of R404A. Therefore, HFC-161 mixture can be used as a potential alternative refrigerant to R502.